Nationwide biopsy survey of renal diseases in the Czech Republic during the years 1994-2011 - Maixnerova, Dita; Jancova, Eva; Skibova, Jelena; Rysava, Romana; Rychlik, Ivan; Viklicky, Ondrej; Merta, Miroslav; Kolsky, Alexander; Reiterova, Jana; Neprasova, Michaela; Kidorova, Jana; Honsova, Eva; et al. (Journal of nephrology, 2015)
BACKGROUND: We describe data on 10,472 renal biopsies gathered by the Czech Registry of Renal Biopsies over a period of 18 years. METHODS: We assessed the main demographic, clinical and histological data of individuals who underwent renal biopsies of native kidneys in 31 centers in the Czech Republic (population 10.3 million) during the period 1994-2011. RESULTS: We evaluated 10,472 renal biopsies: males 57.8%, children (≤15 years) 13.6%, elderly (>60 years) 19.1%. The most frequent biopsy-proven diseases were primary (55.7%) and secondary (29.1%) glomerulonephritides (GN). Tubulointerstitial nephritis (TIN) was observed in 3.4 % and vascular diseases in 4.1%. The samples were non-diagnostic in 4.2%. Among primary GN the most frequent diagnoses were IgA nephropathy (IgAN) (37.4%), membranous GN (MGN) (13%) and focal segmental glomerulosclerosis (FSGS) (12.6%). Among secondary GN, systemic lupus erythematosus (SLE) represented 23.2%, hereditary diseases 19.8% and necrotizing vasculitis (NV) 19.4%. Among adults, mild renal insufficiency [serum creatinine (SCr) 111-200 μmol/l] was present in 24.7%, advanced renal insufficiency (SCr 201-400 μmol/l) in 15.3, and 12.3% of patients had SCr > 400 μmol/l. The most common diseases in patients with nephrotic proteinuria were minimal change disease (MCD) (39.7%) among children, IgAN (26.2%) in adults aged 16-60 years and amyloidosis (42.7%) among the elderly. The mean annual incidence (per million population) was: primary GN 30.9, secondary GN 18.1, IgAN 11.6, MGN 4.0, SLE 4.0, FSGS 3.9, MCD 3.4, NV 3.2, diabetic nephropathy 2.3, thin basement membrane glomerulopathy 2.0, mesangioproliferative GN 1.9, and TIN 1.9. Ultrasound needle guidance was used in 66.8%. The frequency of serious complications (symptomatic hematoma, gross hematuria, blood transfusion) was approximately 3.2%. CONCLUSIONS: This report provides representative population-based data on native biopsy-proven renal diseases in the Czech Republic. Over the 18 years of nationwide biopsy survey, we noted an increase of the mean age of renal biopsy cases, an increasing proportion of elderly, and a cardinal change in biopsy technique towards ultrasonography needle guidance.
Keywords: Infant; Adolescent; chronická renální insuficience; Adult; senioři; Registries; incidence; Aged; Male; glomerulonefritida; dědičná nefritida; Nephritis, Hereditary; lidé; Glomerulonephritis; lidé středního věku; Humans; Child; Vasculitis; Incidence; ledviny; Amyloidosis; Middle Aged; diabetické nefropatie; Young Adult; Child, Preschool; Nephrosis, Lipoid; nemoci ledvin; Czech Republic; amyloidóza; senioři nad 80 let; registrace; Aged, 80 and over; mužské pohlaví; Image-Guided Biopsy; dospělí; kojenec; mladý dospělý; lipoidní nefróza; dítě; Necrosis; nekróza; Česká republika; ženské pohlaví; mladiství; vaskulitida; Diabetic Nephropathies; Female; Renal Insufficiency, Chronic; Kidney; ultrazvukem navigovaná biopsie; Kidney Diseases; předškolní dítě